The Influence of Social Media Use on Preventive Behavior Against the Spread of Malaria in the Working Area of Mutiara Community Health Center, Asahan Regency, 2025 - Zakiah Pulungan; Reni Aprinawaty Sirait; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2026)
Malaria is one of the infectious diseases that remains a public health problem in many countries, particularly in tropical and subtropical regions. This disease is caused by the Plasmodium parasite, which is transmitted through the bite of an infected female Anopheles mosquito.This study aimed to analyze the influence of social media use on preventive behavior in preventing the spread of malaria. The study employed a cross-sectional design and was conducted at Mutiara Community Health Center, Asahan Regency, in 2025. The research was carried out from January to April 2025. The study population consisted of all patients seeking treatment at Mutiara Community Health Center, with a total sample of 100 respondents selected using a simple random sampling technique. Data analysis was performed using the Chi-square test and logistic regression.The results showed that there was no significant association between gender (p = 0.159; OR = 1.96; 95% CI = 0.863–4.434) and age (p = 0.840; OR = 1.09; 95% CI = 0.464–2.570) with preventive behavior against malaria transmission. However, there was a significant association between educational level (p = 0.009) and social media use (p = 0.047; OR = 2.70; 95% CI = 1.070–6.856) with preventive behavior against malaria transmission.Based on these findings, respondents are expected to increase their awareness and active participation in implementing preventive behaviors to reduce the spread of malaria, such as maintaining environmental cleanliness and using mosquito nets while sleeping.